A network meta‐analysis of interproximal oral hygiene methods in the reduction of clinical indices of inflammation. Issue 5 (31st May 2018) - Kotsakis, Georgios A.; Lian, Qinshu; Ioannou, Andreas L.; Michalowicz, Bryan S.; John, Mike T.; Chu, Haitao
Abstract: Background: A wide selection of Interdental Oral Hygiene (IOH) aids is available to consumers. Recommendations for selection are, however, limited by the lack of direct comparisons in available studies. We aimed to assess the comparative efficacy of IOH aids using Bayesian Network Meta‐Analysis (BNMA). Methods: Two independent reviewers performed a systematic literature review of randomized clinical trials assessing IOH aids, based on a focused question. Gingival inflammation (Gingival Index (GI), Bleeding‐on‐probing (BOP)) was the primary outcome and plaque and probing depth were secondary outcomes A random‐effects arm‐based BNMA model was run for each outcome; posterior medians and 95% credible‐intervals (CIs) summarized marginal distributions of parameters. Results: A two‐phase selection process identified 22 trials assessing 10 IOH aids as brushing adjuncts. Interdental brushes (IB) yielded the largest reduction in GI (0.23 [95% CI: 0.09, 0.37]) as toothbrushing adjuncts, followed by water‐jet (WJ) (0.19 [95% CI: 0.14, 0.24]). Rankings based on posterior probabilities revealed that IB and WJ had the highest probability of being "best" (64.7% and 27.4%, respectively) for GI reduction, whereas the probability for toothpick and floss being the "best" IOH aids was near zero. Notably, except for toothpicks, all IOH aids were better at reducing GI as compared with control. Conclusions: BNMA enabled us to quantitatively evaluate IOH aids and provide a global ranking of their efficacy. Interdental brushes and water‐jets ranked high for reducing gingival bleeding, whereas toothpicks and floss ranked last. The patient‐perceived benefit of IOH aids is not clear because gingival inflammation measures are physical indicators of periodontal health.